2017
DOI: 10.7554/elife.29744
|View full text |Cite
|
Sign up to set email alerts
|

Sculpting ion channel functional expression with engineered ubiquitin ligases

Abstract: The functional repertoire of surface ion channels is sustained by dynamic processes of trafficking, sorting, and degradation. Dysregulation of these processes underlies diverse ion channelopathies including cardiac arrhythmias and cystic fibrosis. Ubiquitination powerfully regulates multiple steps in the channel lifecycle, yet basic mechanistic understanding is confounded by promiscuity among E3 ligase/substrate interactions and ubiquitin code complexity. Here we targeted the catalytic domain of E3 ligase, CHI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 64 publications
0
39
0
Order By: Relevance
“…Indeed, we have previously shown that the nanobody‐based targeted ubiquitination approach can be used to inhibit KCNQ1 channels by eliminating them from the cell surface (Kanner et al . 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, we have previously shown that the nanobody‐based targeted ubiquitination approach can be used to inhibit KCNQ1 channels by eliminating them from the cell surface (Kanner et al . 2017).…”
Section: Resultsmentioning
confidence: 99%
“…2012; Kanner et al . 2017). In heterologous cells, nb.F3‐Nedd4L decreased the surface density of reconstituted Ca V 2.2 and Ca V 1.2 channels without enhancing the degradation of the pore‐forming α 1B and α 1C subunits, respectively (Fig.…”
Section: Voltage‐gated Calcium Channels: Basic Structure Function Anmentioning
confidence: 99%
“…A distinct advantage of uAbs is their highly modular architecture which enables target selection to be rewired by simply swapping the synthetic protein‐binding domain. For example, targeted proteolysis has been achieved for a diverse array of protein substrates including eukaryotic proteins (ASC, HRAS/KRAS, Lck, and SHP2,), intraneuronal bacterial proteins ( Clostridium botulinum neurotoxin [BoNT] proteases), fluorescent proteins (FPs), and dozens of FP‐tagged proteins that range in size from 27 to 179 kDa and localize in different subcellular compartments including the cytoplasm, nucleus, and cell membrane . Moreover, by incorporating synthetic binding proteins that recognize particular protein states (e.g., active vs. inactive conformation, mutant vs. wild‐type, posttranslationally modified, and so forth), it becomes possible to deplete certain protein subpopulations while sparing others .…”
Section: Engineering Posttranslational Protein Degradation Strategiesmentioning
confidence: 99%
“…However, they also offer a generic means of targeting in live cells the huge variety of available tagged proteins and the many emerging examples of endogenous proteins tagged with FPs by gene editing. GFP-targeting nanobodies have been used for applications such as targeted proteosomal degradation [23, 24] and relocation of proteins in cells [25], but these and other applications are less developed for RFP-targeting nanobodies.…”
Section: Introductionmentioning
confidence: 99%